A STUDY ON EQUIVALENT FLEXURAL RIGIDITY OF COMPLEX POLYGONAL HONEYCOMB STRUCTURE - GUO YuChao; WANG LiKai; DUAN ShiHui (Jixie qiangdu)
The equivalent flexural rigidity of a complex polygonal honeycomb structure is investigated in this study. The honeycomb is equivalent to a orthogonal anisotropic plate for calculating the deformation energy under uniform bending moment,and the deformation energy of each wall is summed,then the analytical expressions for the equivalent flexural stiffness of honeycomb structure were derived based on the energy equivalence principle. The angle and length of walls has a great influence on equivalent flexural stiffness,the changes of angle and length will lead to positive and negative changes of the coupling stiffness,the absolute value of flexural stiffness increases with the increase of the wall’s height and thickness. The validity of the present analysis is demonstrated by the inversion results obtained by the finite element method.